Fatty acid binding proteins (FABPs) – a new laboratory biomarker for kidney diseases - Dobrek, Łukasz (Journal of Medical Science, 2017)
Fatty acid binding proteins (FABPs) are a family of intracellular proteins involved in metabolism of lipids. By regulating the intracellular level of free fatty acids, those proteins indirectly influence intracellular signaling pathways. FABPs also play a role in regulation of cell growth and differentiation, and exert a significant antioxidant effect. Some reports suggest that FABPs are released by various organs (heart, liver, intestines, kidneys) in response to tissue damage. The article briefly summarizes the structure, classification and function of FABPs and discusses the applicability of liver- (L-FABP) and heart-type (H-FABP) FABPs in laboratory diagnosis of selected clinical entities, particularly kidney diseases.